Islands and Horizons: Metacuratorial as an Approach, a Perspective and a Navigational Tool for Curatorial Practice - Erdogan, Elif (Taideyliopiston Kuvataideakatemia, 2024)
“Islands and Horizons: Metacuratorial as an Approach, a Perspective and a Navigational Tool for Curatorial Practice” studies curatorial practices with a special focus on the concept of metacuratorial, a neologism coined by the author to denote a critical, self-reflexive approach to curatorial, i.e. applying curatorial on curatorial. In this sense, the project conceptualizes curating as more than exhibition-making. The metacuratorial places itself at a broader scope for understanding all the activities, the contexts and the implications of the choices made in the course of any curatorial practice. The project is divided into three major parts: Part A considers the social contemporary today, touching upon themes of agony, paradigm shifts, and uncertainty and acknowledges art and exhibitions as possible solutions to these crises. Part B addresses the metacuratorial, which is situated above the curatorial practice, and provides its theoretical foundations. It discusses the ways in which this upper-level perspective on analysis subverts the parameters of curatorial practice by interrogating the culture and the systems, as well as the histories, within which curators work. This part also describes functions of such an approach on various scales: that of a curator, an institution, and perhaps, a higher level of governance. In Part C the author presents three curated projects that she has worked on during her practice as a curator for the Yapi Kredi Arts and Culture in Istanbul. The respective exhibitions serve as illustrations of the metacuratorial practice in practice, and thus its relevance and, conciliating, the need for reconsidering curatorial practices and the cultural institutions that support them.
Keywords: taidenäyttelyt; kuratointi; näyttelyt; näyttelytoiminta; Praxis